Study on the preparation of calcium modified coal gangue and its adsorption performance of phosphate - Yanrong Dong; Hongyu Zhai; Ziqing Gao; Guohao Gong; Fengjuan Li (Scientific Reports)
Abstract The adsorption of phosphate in the collected water is crucial to alleviate the crisis of phosphorus resources, which is in line with the concept of green and sustainable development of resources. In this study, based on the calcium modification technology of pyrolysis combined with chemical modification, a new type of calcium modified coal gangue (CaMCG) was prepared by using coal gangue as raw material and calcium chloride as modifier for the removal of phosphate.The optimum preparation conditions of CaMCG were obtained by response surface test: mcalcium chloride:mcoal gangue=1, calcination temperature 735℃, calcination time 135 min. Batch adsorption experiments showed that when the phosphate concentration was 100 mg/L, the optimal CaMCG dosage was 0.5 g and the optimal reaction time was 48 h. At pH 3–7, the adsorption capacity of CaMCG for phosphate was always good. The order of the strength of coexisting anions affecting the adsorption of phosphate by CaMCG was: CO3 2− > SO4 2− > HCO3 − > NO3 − ≈ Cl−. Kinetic isotherm analysis showed that the adsorption of phosphate by CaMCG had both physical adsorption and chemical adsorption. The theoretical maximum adsorption capacity of CaMCG for phosphate was 17.85 mg/g. The adsorption process of CaMCG on phosphate conformed to the Langmuir model. The main mechanisms of CaMCG adsorbing phosphate are electrostatic interaction, surface precipitation, adsorption exchange and complexation. This study shows that CaMCG has great potential in adsorbing phosphate, which can provide technical reference for the efficient utilization of coal gangue and the treatment of phosphate wastewater.The phosphate adsorbed by CaMCG can be recycled and reused to achieve efficient and sustainable recycling of phosphorus resources.